Commentary on "Consumer behaviour analysis and non-adoption of behavioural interventions: implications for managerial action". Issue 3 (20th June 2019) - Beadle-Brown, Julie; Bradshaw, Jill
Abstract : Purpose: The purpose of this paper is to reflect on the difficulties highlighted by Ntinas around supporting change in services for people with intellectual and developmental disabilities. Design/methodology/approach: This commentary examines what is needed for change and reflects on staff culture. Findings: The authors propose that it is not sensible to separate the culture of a service from the implementation of person-centred approaches and attempt to map how the concepts overlap and are interconnected. Originality/value: Whilst some elements of culture are clearly important in order to start the process of change, other elements will change as an intervention is introduced and embedded.